Descriptive study of women with eclampsia requiring intensive care unit admission at Chris Hani Baragwanath academic hospital - (:unkn) unknown (My University, 2019)
Eclampsia is a life threatening condition and the most widely recognized complication of hypertensive disorders of pregnancy requiring intensive care admissions. It is also an important cause of maternal and perinatal morbidity and mortality, and accounts for approximately 63000 maternal deaths every year globally. Objectives To determine the incidence, outcomes and complications of women with eclampsia admitted to the intensive care unit at Chris Hani Baragwanath Academic Hospital (CHBAH). Methods A retrospective cross sectional study of all women with eclampsia admitted to the intensive care unit at CHBAH. Results There were 57 women with eclampsia admitted to ICU between January 2011 and December 2016. Eclampsia with ICU admissions was most common between the ages of 16-20 years (n=18, 31.5%) and more prevalent in primigravida. The incidence rate of ICU admission in women with eclampsia is 44/100 000 births per year. There were three maternal deaths from eclampsia. Maternal and fetal complications that developed in ICU were HELLP syndrome (n=15, 26.3%), acute renal failure (n=11, 19.2%), metabolic acidosis (n=9, 15.8%), pulmonary oedema (n=8, 14%), preterm births (n=31, 52.5%), birth asphyxia (52.5%) and low birth weight (45.8%). The reason for ICU admission was haemodynamic monitoring (100%), ventilation (89%), cardiopulmonary resuscitation (45%), renal support (19%) and inotropes (16%). Conclusion Eclampsia is a preventable condition affecting women mostly in low to middle income countries. Eclampsia that requires ICU admission is often associated with life-threatening multi-organ system maternal and fetal complications. Measures to prevent eclampsia need to be strengthened.
The study is submitted in partial fulfilment for the degree of Masters of Medicine in Obstetrics and Gynaecology 2019
Keywords: Eclampsia--therepy; Critical care; Eclampsia--Diagnosis